Britain's departure from Aden and South Arabia : without glory but without disaster - Brehony, Noel; Jones, Clive, 1965- (Middle Eastern & Islamic Studies at Gerlach Press, 2020)
Britain's hasty departure from Aden and South Arabia after 138 years has often been presented as a humiliation at best and a disaster at worst. London?s hopes of handing power and sovereignty over to a friendly federal regime collapsed in the face of a nationalist uprising backed that enjoyed the support of Egypt. Five decades after the final British troops left Aden, academic experts and former British officials directly involved in the events that unfolded critically reflect on British withdrawal from South Arabia, the post-colonial problems in South Yemen that still resonate today, and how the United Kingdom learnt from its experience in stabilising Oman while overseeing the formation of the United Arab Emirates.